Model Pendampingan Koperasi Dalam Upaya Akselerasi Pencapaian Koperasi Modern - Restiany, Devi; Irawan, Dandan; Supriyadi, Deddy; Riyadhi Prayanda, Ibnu (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Intervention efforts in dealing with the problems of modern cooperatives focus on priority needs, and one method is through assistance programs.This research uses qualitative methods with data collection techniques in the form of interviews, document analysis, observation, and triangulation. The results show that the 2023 modern cooperative assistance program is